Effect of Robusta Coffee Extract (Coffea canephora) on Mice (Mus musculus) on Gastric Histopathology and Anxiety Level - Soebroto, Difa Hasna; Harlita, Harlita (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2025)
Robusta coffee (Coffea canephora) contains bioactive compounds, such as caffeine that have the potential to affect the digestive system and anxiety levels. This study aims to evaluate the effects of robusta coffee extract on gastric histopathology and anxiety levels in mice (Mus musculus). The method used involved 4 treatments, K1: negative control (without treatment), K2: positive control with aspirin 10.84 mg/20gr body weight of mice, K3: coffee extract 6.72 mg/20gr body weight of mice, K4: coffee extracts 13 mg/20gr body weight of mice. The results showed that robusta coffee extract impacted the histological structure of the stomach, with indications of changes in the gastric mucosa. In addition, there was a tendency for changes in the level of anxiety in mice analyzed through the behaviour test, Elevated Plus Maze test. This study provides insight into the potential physiological effects of robusta coffee consumption and its implications for gastric health and psychological conditions.